Using statistics in criminal justice - Murray, Rebecca (Aspen College series, 2016)
Preface -- Acknowledgments -- Tools of the trade -- Uses of statistics in criminology, criminal justice, and legal research -- Context and role of statistics in criminal justice research -- Sketching it out -- Finding and categorizing data -- Measures of central tendency -- Measures of variation -- Color it in -- The normal curve and standard scores -- Samples and hypothesis testing -- Differences between means: two samples -- Differences between means: three or more samples -- Non-parametric methods of comparison for nominal data -- Non-parametric methods of comparison for ordinal and interval-ratio data -- Detail work -- Correlation -- Regression -- Statistics and evaluation research -- Appendix A: Area under the normal curve / Critical Values of z -- Appendix b: critical values of student?s t -- Appendix C: Critical values of F -- Appendix D: Distribution of q scores -- Appendix E: Critical values of pearson's chi-squared (also used for Kuskal-Wallis H) -- Appendix F: Critical values of Mann-Whitney U -- Appendix G: critical values of spearman's RHO -- Appendix H: Critical values of pearson's R -- Appendix I: answers to end of chapter exercises -- Glossary -- Index